Musicalligraphics: Improvising Across Modalities - Stewart, Jesse; Davies, Jim; Akbari, Jamaal Amir (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
This essay and its accompanying images and videos include documentation of, and reflections upon, the musicalligraphics project: a live collaborative performance of improvised music, improvised calligraphy, and improvised spoken word. Analyzing the footage of these various performances, the authors examine the ways in which our improvisatory choices influenced one another across artforms and sensory modalities. In keeping with the collaborative nature of the project, we have adopted a flexible authorial voice in this paper that oscillates between our individual perspectives and shared insights. Through this discussion, we consider the challenges and opportunities of cross-discipline collaboration, founded upon our experiences collaborating extemporaneously through spoken word, music, and calligraphy.